The Influence of Organizational Culture on Teachers Job Satisfaction - Anitia Fadhila Bumay (CV. Alim's Publishing, 2026)
Job satisfaction is an essential factor influencing the quality of teaching, professional performance, and the achievement of educational goals. One factor that is believed to contribute to teachers' job satisfaction is the organizational culture established within the school environment. This study aims to examine the effect of organizational culture on teachers' job satisfaction among junior high school teachers in North Lampung Regency. The research employed a quantitative approach with an ex post facto design. A total of 312 teachers were selected as the research sample using the cluster random sampling technique. Data were collected through questionnaires developed based on the indicators of the research variables. The data were analyzed using simple linear regression to determine the effect of organizational culture on teachers' job satisfaction. The findings reveal that organizational culture has a positive and significant effect on teachers' job satisfaction. These results indicate that a stronger and more supportive organizational culture is associated with higher levels of teacher job satisfaction. Therefore, strengthening a conducive, collaborative, and professionally oriented organizational culture is an important strategy for enhancing teachers' job satisfaction while supporting the continuous improvement of educational quality.